PENGARUH FUNGI MIKORIZA ARBUSKULA DAN PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL KACANG TANAH (Arachis hypogaea L.) - Halim, Halim; F.S, Rembon; Resman, Resman (AgriPeat, 2020)
This study was aimed to determine the effect of arbuscular mycorrhizal fungi and liquid organic fertilizer on the growth and yield of peanut. This research was used the randomized block design (RBD) in factorial pattern with two factor i.e.: the first factor are the doses of the Arbuscular mycorrhiza fungi (AMF) (M) with three levels: without FMA propagules (M0), FMA propagules 20 g/planting hole (M1), FMA propagules 40 g/planting hole (M2) and the second factor are doses of liquid organic fertilizer (LOF) (P) with three levels: without LOF (P0), LOF 50 ml/L water) (P1), LOF 100 m /L water) (P2). The variables observed in this study were: plant height measured at 14, 28, 42, 49 Days after Planting (DAP), number of nodules, seed weight, and dry seed production (ton ha-1). The results showed that the application of liquid organic fertilizer 50 ml/ L water (P1) gave the best plant height as 39.87 cm. Application of a combination of liquid organic fertilizer 100 ml/L water with mycorrhizal fungi dose 40 g/planting hole (P2M2) is the highest average dry seed production as 5.47 tons ha-1.